Chemical-Functional Analysis of Extracts Obtained from Zuccagnia punctata Powder Using Green Solvents (NaDESs) in Conjunction with Traditional and Non-Traditional Techniques - Romero, Antonela Mariana (2024)
Zuccagnia punctata Cav. (Family Fabaceae. Subfamily Caesalpinioideae) is a native plant species with a long history of use in Argentine traditional medicine. The purpose of the present study was to extract bioactive compounds with antioxidant and antifungal activity from Z. punctata aerial parts using conventional solvents (water, ethanol 60◦, vegetal oil) and unconventional solvents (natural deep eutectic solvents or NaDESs) such as green solvents with and without the assistance of ultrasound (UAE) and microwaves (MAE). NaDESs such as glucose: lactic acid (LGH), sucrose: citric acid (CAS), choline chloride: urea (CU) and glucose: fructose: sucrose (FGS) were used. LGH and CU were effective in the extraction of phenolic compounds (6710 ± 10.12 µg GAE/mL and 7140 ± 15.00 µg GAE/mL, respectively) as well as ethanol (6270 µg ± 12.00 µg GAE/mL) using conventional methods. Two chemical markers of Z. punctata (2′,4′-dihydroxychalcone and 2′,4 dihydroxy-3-methoxychalcone) were extracted in a high proportion in ethanol, oil, LGH and CU with UAE. The ABTS antioxidant capacity was higher in the extracts obtained with LGH and CU (SC50: 0.90 ± 0.10 µg GAE/mL and 1.08 ± 0.16 µg GAE/mL, respectively). The extract obtained with vegetal oil was the most potent as antifungal, followed by the extracts in ethanol, LGH and CU. These findings highlight the importance of using environmentally friendly solvents such as NaDESs to obtain bioactive metabolites from Z. punctata, an endemic plant of Argentina with a potential application in the food, cosmetic and pharmaceutical industries.